The last story of Mina Lee - Kim, Nancy Jooyoun (Park Row Books, 2020)
Margot Lee's mother isn't returning her calls. It's a mystery to twenty-six-year-old Margot, until she visits her childhood apartment in Koreatown and finds her mother dead under suspicious circumstances. The discovery sends Margot digging through the past, unraveling the facts of Mina's life as a Korean War orphan and undocumented immigrant, only to realize how little she truly knew about her mother.